2x+75=6x-1

Simple and best practice solution for 2x+75=6x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+75=6x-1 equation:


Simplifying
2x + 75 = 6x + -1

Reorder the terms:
75 + 2x = 6x + -1

Reorder the terms:
75 + 2x = -1 + 6x

Solving
75 + 2x = -1 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
75 + 2x + -6x = -1 + 6x + -6x

Combine like terms: 2x + -6x = -4x
75 + -4x = -1 + 6x + -6x

Combine like terms: 6x + -6x = 0
75 + -4x = -1 + 0
75 + -4x = -1

Add '-75' to each side of the equation.
75 + -75 + -4x = -1 + -75

Combine like terms: 75 + -75 = 0
0 + -4x = -1 + -75
-4x = -1 + -75

Combine like terms: -1 + -75 = -76
-4x = -76

Divide each side by '-4'.
x = 19

Simplifying
x = 19

See similar equations:

| .16(x-5)=.50(x+6) | | f(x)=x^5+3x^4-2x^2+4x-7 | | 5X^2+3X-X=0 | | 9x-6+9x+5=9x+9x-4 | | (2x-4)=x+61 | | 9.3m+7.8-2.3m=-9.6+7m+17.4 | | x*4=212 | | 1/6(x-5)=1/2(x=6) | | -5x+2(3x-6)=-7-4x | | 2x+4+x+8=5x+2 | | 8x-(3x+3)=6x-17 | | q^3*p^3=35 | | 23x=13 | | 7x-6=8(x+4) | | 3(x+1)=-2(2x+2) | | h(-3)+8=-2x-5 | | 4.5m+7.4-7m=-1.3-2.5m+8.7 | | -2x+7(-3x-7)=-69-3x | | 4x+8+8x+9=9x+3x+14 | | -7m+12+8m-3= | | 4x-24=56+2x | | (x)6=3/7 | | 4b-6=7b | | f(x)=x^3+16x^2+84x+143 | | -(-8x-6y-43)= | | 6z-8z=6z-9-z | | 7x+8-6x+4= | | 8r+6=86 | | -9(2x-3)= | | 8(6+c)=7(c-6) | | 8x+4=9(x+9) | | 56=4y+3y |

Equations solver categories